2014
DOI: 10.2139/ssrn.2427421
|View full text |Cite
|
Sign up to set email alerts
|

Input Specificity and the Propagation of Idiosyncratic Shocks in Production Networks

Abstract: This article examines whether firm-level idiosyncratic shocks propagate in production networks. We identify idiosyncratic shocks with the occurrence of natural disasters. We find that affected suppliers impose substantial output losses on their customers, especially when they produce specific inputs. These output losses translate into significant market value losses, and they spill over to other suppliers. Our point estimates are economically large, suggesting that input specificity is an important determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
3
30
0
1
Order By: Relevance
“… These results are consistent with the empirical findings of Barrot and Sauvagnat (), who found that negative shocks to a firm have a greater impact on its partners if the affected firm produces less substitutable goods. …”
supporting
confidence: 92%
“… These results are consistent with the empirical findings of Barrot and Sauvagnat (), who found that negative shocks to a firm have a greater impact on its partners if the affected firm produces less substitutable goods. …”
supporting
confidence: 92%
“… The empirical literature on production networks, like Atalay (), Boehm, Flaaen, and Pandalai‐Nayar (), and Barrot and Sauvagnat (), all find that structural elasticities of substitution in production are significantly below 1, and sometimes very close to zero, across intermediate inputs, and between intermediate inputs and labor at business‐cycle frequencies. Furthermore, a voluminous literature on structural transformation, building on Baumol (), has found evidence in favor of non‐unitary elasticities of substitution in consumption and production across sectors over the long run. …”
mentioning
confidence: 99%
“…(), Ahern () shows that firms that are in central industries earn higher equity returns because they are more exposed to market risk. Barrot and Sauvagnat () show that input specificity in production networks propagates idiosyncratic shocks between suppliers and customers.…”
mentioning
confidence: 99%